(untitled) (Research, Society and Development, 2019)
The association of digital resources in mathematics classes is already a subject much discussed in Brazil. Among the possibilities of these resources is the virtual learning environment, which adds several learning objects that can aid in the teaching and learning processes. In this work, we aim to present, from the learning object LogCALC! a script of an activity for the study of Logarithms. For this, Didactic Engineering was used as methodology, specifically two of the four phases, namely a priori analysis and a posteriori analysis. From the production of a teaching sequence, it was proposed how to use the learning object LogCALC! which is linked to the studies Logarithms. As characteristics of the OA contribute to this understanding of Logarithms contents, the interface between the computer and the students is highlighted, through the proposition of challenging situations involving real issues such as earthquakes and acid rain. It is hoped to expand the possibilities of teachers’ work and study of students from different schools, because it is understood that LogCALC! can be used to support users’ learning, favoring, among others, the contextualization and significance of this content.